Analysis of Cross-Cultural Communication in English Subjects and the Realization of Deep Learning Teaching - Niu, Jianing; Liu, Yang (Computational intelligence and neuroscience, 2022)
In subject teaching, subject characteristics are the logical starting point for teaching development, and a deep understanding of subject characteristics is the basis for effective teaching. In practice, due to ignoring the cross-cultural understanding of middle school English subjects, there has been a long-term dilemma of “emphasizing knowledge and neglecting culture,” and overemphasis on the instrumental nature of middle school English has caused middle school English teaching to lose cultural self-cultivation and obscured the due education human value. Under the background of globalization and diversification, it is more and more important to develop students’ cross-cultural awareness. How to realize cross-culturalism in middle school English teaching has become an important subject of teaching reform and development. From the perspective of English subject, this research constructs a scientific and implementable English listening and speaking teaching mode that promotes students’ in-depth learning, provides specific and operational teaching implementation plans for English subject teachers in front-line teaching, and improves classroom teaching. It can promote students’ construction of the meaning of language knowledge, stimulate their learning motivation, and finally achieve the common development of teachers and students.